A Shift Toward a Plant-Centered Diet From Young to Middle Adulthood and Subsequent Risk of Type 2 Diabetes and Weight Gain: The Coronary Artery Risk Development in Young Adults (CARDIA) Study - Choi, Yuni (Diabetes Care, 2020)
OBJECTIVE: To examine the associations between change in plant-centered diet quality and type 2 diabetes risk and change in body size. RESEARCH DESIGN AND METHODS: A prospective study conducted in the U.S. enrolled adults ages 18–30 years in 1985–1986 (examination year [Y0]) and followed them through 2015–2016. We analyzed the associations between change in plant-centered diet quality over 20 years (Y0–Y20) and diabetes (Y20–30; n = 2,534) and change (Y0–Y20 and Y20–30) in BMI, waist circumference (WC), and weight (n > 2,434). Plant-centered diet quality was measured using the A Priori Diet Quality Score (APDQS); a higher score favors nutritionally rich plant foods. Cox regression models were used to assess diabetes risk, and linear regression models were used to examine change in body size. RESULTS: During a mean follow-up of 9.3 (± 1.7) years, 206 case subjects with incident diabetes were observed. In multivariable analysis, participants with the largest increase in APDQS over 20 years had a 48% (95% CI 0.31–0.85; P(trend) < 0.001) lower risk of diabetes over the subsequent 10 years compared with participants whose score remained stable. Each 1-SD increment in APDQS over 20 years was associated with lower gains in BMI (−0.39 kg/m(2); SE 0.14; P = 0.004), WC (−0.90 cm; SE 0.27; P < 0.001) and weight (−1.14 kg; SE 0.33; P < 0.001) during the same period, but not with subsequent changes. CONCLUSIONS: Young adults who increased plant-centered diet quality had a lower diabetes risk and gained less weight by middle adulthood.